The influence of disease type and activity to sexual life and health quality in inflammatory bowel disease - , Esra Ateş Bulut, Murat Törüner (Turkish Journal of Gastroenterology 1, 2019)
Background/Aims: Inflammatory bowel disease (IBD) has a major impact on patients’ quality of life (QoL), mood, and sexual life. The purpose of the present study was to show the effect of disease type and activity on sexual life and QoL in patients with IBD. Materials and Methods: A total of 122 patients with IBD and 42 sex- and age-matched control cases were included in the study. Demographic characteristics were recorded. The disease activity of patients with IBD was assessed by the Harvey-Bradshaw Index in Crohn’s disease (CD) and the Mayo Clinical Ulcerative Colitis Activity Index in ulcerative colitis (UC). All participants were subjected to complete three questionnaires: Short Form 36 (SF-36), Hospital Anxiety and Depression Scales (HAD-A and HAD-D), and Arizona Sexual Experience Scale (ASEX). Results: There was no difference in terms of demographic characteristics between the three groups, except cigarette exposure in CD. The disease activity of patients with UC and CD was not different (p>0.05). The mean HAD-A score was significantly higher in the CD group, whereas the mean HAD-D score was higher in the IBD group than in the control group (p<0.05). Anxiety was seen more frequently in women. SF-36 scale scores were found to be lower in the UC and CD groups than in the control group (p<0.05). The mean ASEX scores of women with UC (19.59±7.59) and CD (19.38±6.27) were both significantly higher than those of the control group (15±4.76). Although the mean ASEX scores of men were not different, some ASEX subscores of the IBD groups were worse than those of the control. Conclusion: Inflammatory bowel disease is a chronic disease that has multiple complications affecting patients’ psychosocial life. Patients have more anxiety, depression, and sexual dysfunction when their disease is active. Patients should be screened for psychological diseases and sexual dysfunction, and necessary treatments should be given. Cite this article as: Ateş Bulut E, Törüner M. The influence of disease type and activity to sexual life and health quality in inflammatory bowel disease. Turk J Gastroenterol 2019; 30: 33-9.